Impact of The Covid-19 Pandemic on Contraception Users: A Scoping Review - Lantiar Winda Oktari Pondawati Pondawati; Ismarwati Ismarwati (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background: The COVID-19 pandemic impacts health services, especially on the use of contraception. Social policies resulted in a decrease in contraceptive users during the pandemic and difficulties in accessing health facilities to obtain the desired contraception. Purpose: This scoping review aims to review the evidence regarding the impact of the pandemic on contraceptive users. Methods: The criteria included in this review are Indonesian or English articles with the last 3 years of publication, articles focused on the impact of the pandemic on user usage. The Exclude criteria are article opinion, books, or review article. This scoping review's structure uses the PRISMA-ScR Checklist with 5 stages, according to Arksey and O'Malley. The search for articles was carried out on December 10, 2021, using several databases, including PubMed, Wiley Online Library, ProQuest, and ScienceDirect. Results: 49 out of 1145 articles are relevant, and ten articles meet the inclusion criteria. The result is presented with three themes: discontinuation of contraception, unplanned pregnancy, and abortion. Conclusion: From several articles obtained during the search, several problems were found regarding contraceptive users during the covid 19 pandemic: the lack of access to contraception, an increase in the rate of discontinuation of contraceptive use, a high number of unplanned pregnancies, and an increase in abortion services.